Emigration and wages: The EU enlargement experiment - Benjamin Elsner (Institute for the Study of Labor (IZA), 2011)
The enlargement of the European Union provides a unique opportunity to study the impact of the lifting of migration restrictions on the migrant sending countries. With EU enlargement in 2004, 1.2 million workers from Eastern Europe emigrated to the UK and Ireland. I use this emigration wave to show that emigration significantly changed the wage distribution in the sending country, in particular between young and old workers. Using a novel dataset from Lithuania, the UK and Ireland for the calibration of a structural model of labor demand, I find that over the period of five years emigration increased the wages of young workers by 6%, while it had no effect on the wages of old workers. Contrary to the immigration literature, there is no significant effect of emigration on the wage distribution between high-skilled and low-skilled workers.
urn:nbn:de:101:1-201111303434
Keywords: F22; J31; O15; R23; 330; emigration; EU enlargement; European integration; wage distribution; EU-Erweiterung; Internationale Wanderung; Lohnniveau; EU-Staaten